2014
DOI: 10.1186/1471-2164-15-950
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization and RNA-Seq profiling of the HD-Zip transcription factor family in soybean (Glycine max) during dehydration and salt stress

Abstract: BackgroundThe homeodomain leucine zipper (HD-Zip) transcription factor family is one of the largest plant specific superfamilies, and includes genes with roles in modulation of plant growth and response to environmental stresses. Many HD-Zip genes are characterized in Arabidopsis (Arabidopsis thaliana), and members of the family are being investigated for abiotic stress responses in rice (Oryza sativa), maize (Zea mays), poplar (Populus trichocarpa) and cucumber (Cucmis sativus). Findings in these species sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
123
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(126 citation statements)
references
References 119 publications
(209 reference statements)
3
123
0
Order By: Relevance
“…Overexpression of some HD-Zip genes have been shown to confer abiotic stress tolerance by activating the expression of stress-responsive gene and/or promoting the ABA biosynthesis (Yu et al 2008;Belamkar et al 2014;Chen et al 2014). Therefore, to better understand the physiological roles of HD-Zip transcription factors during abiotic stress, it was of much importance to develop abiotic stresstolerant plants by engineering manipulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of some HD-Zip genes have been shown to confer abiotic stress tolerance by activating the expression of stress-responsive gene and/or promoting the ABA biosynthesis (Yu et al 2008;Belamkar et al 2014;Chen et al 2014). Therefore, to better understand the physiological roles of HD-Zip transcription factors during abiotic stress, it was of much importance to develop abiotic stresstolerant plants by engineering manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that some members of transcription factor family such as AP2, NAC, NF-Y, and HD-Zip are involved in abiotic stress-mediated responses and play pivotal regulatory roles in the stress tolerance in plants Nakashima et al 2012;Belamkar et al 2014;Chen et al 2014). During the early phase of plant acclimation to drought stress, the stress signals are transduced to trigger the expression of a large number of stress-responsive genes (Kim et al 2002;Harb et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the low cost and high capacity of data, RNA-sequencing (RNA-seq) has been using to measuring differentially expressed genes (DEGs) in response to stress (Marioni et al 2008;Wang et al 2009;Anders and Huber 2010;Rapaport et al 2013). It was also used to reveal differential expressed transcriptome in rice under cold conditions (Shen et al 2014), HD-Zip transcription factors in soybean under salt stress (Belamkar et al 2014) and regulated genes in Brassica juncea under drought stress and high temperature (Bhardwaj et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors (TFs) are important regulatory proteins, and play significant roles in the plant response and adaptation to different types of abiotic stresses (Jeong, Volny, & Lukowitz, 2012;Lee, Park, Yoon, Choi, & Eo, 2013;Lindemose, O'Shea, Jensen, & Skriver, 2013). HD-Zip genes are plant-specific transcriptional factors that play crucial roles in Populus tree development and response to environmental stresses such as water deficit and salt stress (Belamkar et al, 2014;Du, Mansfield, & Groover, 2009;Elhiti & Stasolla, 2009;Hu et al, 2012;Lee et al, 2013;Robischon, Du, Miura, & Groover, 2011). As Populus species are dioecious, male clones in some of the Populus species tend to have longer internodes, higher plant dry weight and heavier wood as compared to the female clones (Gyulai et al, 2015;Khosla & Deol, 1984).…”
Section: Introductionmentioning
confidence: 99%